2005
DOI: 10.1007/s00421-005-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in human skeletal muscle: alternative normalization method and effect of repeated biopsies

Abstract: The reverse transcriptase-polymerase chain reaction (RT-PCR) method has lately become widely used to determine transcription and mRNA content in rodent and human muscle samples. However, the common use of endogenous controls for correcting for variance in cDNA between samples is not optimal. Specifically, we investigated (1) a new normalization method based on determining the cDNA content by the flourophores PicoGreen and OliGreen, (2) effect of repeated muscle biopsies on mRNA gene expression, and (3) the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(174 citation statements)
references
References 30 publications
(39 reference statements)
5
168
0
Order By: Relevance
“…We found that there were no significant changes (P Ͼ 0.05) in mRNA expression between the two baseline muscle biopsy samples (i.e., the second biopsy obtained from the same incision had the same mRNA expression pattern as the original biopsy sample for all 3 genes). Although there have been mixed findings in the literature, changes in mRNA expression are dependent on the variable of interest and the biopsy timing, design, and technique (40,54). Therefore, it appears that our findings are a result of the experimental treatment rather than a prior biopsy effect.…”
Section: Mrna Expression Due To Repeated Muscle Samplingmentioning
confidence: 68%
“…We found that there were no significant changes (P Ͼ 0.05) in mRNA expression between the two baseline muscle biopsy samples (i.e., the second biopsy obtained from the same incision had the same mRNA expression pattern as the original biopsy sample for all 3 genes). Although there have been mixed findings in the literature, changes in mRNA expression are dependent on the variable of interest and the biopsy timing, design, and technique (40,54). Therefore, it appears that our findings are a result of the experimental treatment rather than a prior biopsy effect.…”
Section: Mrna Expression Due To Repeated Muscle Samplingmentioning
confidence: 68%
“…Thus, during a given test session multiple incisions in the same muscle should be made, each 2-3 cm apart, to prevent trauma-induced changes in gene expression 24 . Obtaining multiple biopsies from the same muscle through separate incisions does not apparently alter the transcriptional response of genes responsive to the stress of exercise 24,25 . However, the expression of certain genes may be influenced when a second biopsy is taken through the same incision several hours later 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence-based real-time PCR (ABI PRISM 7900 Sequence Detection System; Applied Biosystems) was used to determine mRNA content of specific genes as described (39). The mRNA content was analyzed using Taqman probes and forward and reverse primers as listed (Table 1), except for FABPpm (Mm00494703_m1), fatty acid transport protein (FATP)1 (Mm00449511_m1), and FATP4 (Mm01327405_m1) mRNA, which were analyzed using premade kits (Applied Biosystems).…”
Section: Muscle Analysesmentioning
confidence: 99%